Helium/Argon-Generated Cold Atmospheric Plasma Facilitates Cutaneous Wound Healing - Lou, Bih-Show (Front Bioeng Biotechnol, 2020)
Cold atmospheric plasma jet (CAPJ) or non-thermal plasma jet has been employed in various biomedical applications based on their functions in bactericidal activity and wound healing. However, the effect of CAPJ generated by a particular composition of gases on wound closure and the underlying mechanisms that regulate wound healing signals remain elusive. In the present study, we investigated the impact of helium (He)- or a gas mixture of He and argon (He/Ar)-generated CAPJ on cell proliferation, which is a pivotal step during the wound healing process. With careful treatment duration control, He/Ar-CAPJ effectively induced keratinocyte proliferation and migration mediated through the activation of epithelial-to-mesenchymal transition (EMT) and cell cycle progression, which was evidenced by a decrease in E-cadherin levels and increases in N-cadherin, cyclin D1, Ki-67, Cdk2, and p-ERK levels. Rat wound healing studies showed that He/Ar-CAPJ treatment facilitated granulation tissue formation and mitigated inflammation in cutaneous tissue, resulting in accelerated wound closure. These findings highlight the possibility that He/Ar-CAPJ can be developed as a therapeutic agent for enhancing wound healing.